Variation in Haemoglobin Reference Ranges and Implications for Use of Health Service Resource in the Republic of Ireland and the UK - O’ Sullivan JM; McNamee T; Harrington JM; Perry IJ; Cahill MR (Journal of Hematology and Oncology Research, 2014)
Variation in the lower and upper limits of haemoglobin (Hb) ranges will alter diagnosis and referral rates of anaemia or erythrocytosis. The haemoglobin ranges for adults in Irish laboratories were applied in the context of haemoglobin levels of a representative sample of Irish adults (SLAN). Between 2.8% and 8.5% of men would be diagnosed with anaemia in different laboratories for lower limit between 130-140g/L. For women, diagnosis of anaemia would range from 0.7% to 7.3% for the lower limit between 110-125g/L. Similar reference range variations occur in UK laboratories. A suggested “normal reference range” is extrapolated from the SLAN cohort.
Keywords: Haemoglobin